(untitled) (Annals of Medical Research, 2025)
Aim: To investigate the impact of maternal subclinical hypothyroidism (SCH) treated with levothyroxine on fetal thyroid dimensions during pregnancy. Materials and Methods: In this prospective observational study, 50 pregnant women with treated SCH and 52 euthyroid controls underwent ultrasonographic evaluation between 20 and 39 gestational weeks were recruited. Fetal thyroid circumference (FTC) and fetal thyroid area (FTA) were measured, and correlations with maternal TSH levels and levothyroxine dosage were analyzed. Results: No significant differences were found between the in fetal thyroid measurements in SCH and control groups before and after adjustment for gestational age. Correlation analyses revealed negligible associations between maternal thyroid function parameters and fetal thyroid size. Although the levothyroxine dose showed a weak negative trend with fetal thyroid measurements, the difference was not statistically significant. The amniotic fluid index (AFI) was significantly higher in the SCH group despite treatment. Conclusion: Adequately treated maternal SCH does not appear to affect fetal thyroid development. These findings support the importance of early diagnosis and levothyroxine therapy for normalizing maternal thyroid function and potentially protecting fetal outcomes.